2017
DOI: 10.1021/jacs.7b06997
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of London Dispersion in Dichloromethane Solutions

Abstract: London dispersion constitutes one of the fundamental interaction forces between atoms and between molecules. While modern computational methods have been developed to describe the strength of dispersive interactions in the gas phase properly, the importance of inter- and intramolecular dispersion in solution remains yet to be fully understood because experimental data are still sparse in that regard. We herein report a detailed experimental and computational study of the contribution of London dispersion to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(189 citation statements)
references
References 86 publications
10
175
0
4
Order By: Relevance
“…To address the reliability of the post-processing protocol for large complexes, Pollice et al 18 devised an example which is largely independent of the assumptions in this protocol. These authors synthesized a proton-bound dimer which can undergo two alternative dissociation reactions (hydrogen bond cleavage or O-NO bond cleavage) upon collision (see Figure 4).…”
Section: Possible Origins Of Discrepancies Between Calculated and Expmentioning
confidence: 99%
“…To address the reliability of the post-processing protocol for large complexes, Pollice et al 18 devised an example which is largely independent of the assumptions in this protocol. These authors synthesized a proton-bound dimer which can undergo two alternative dissociation reactions (hydrogen bond cleavage or O-NO bond cleavage) upon collision (see Figure 4).…”
Section: Possible Origins Of Discrepancies Between Calculated and Expmentioning
confidence: 99%
“…These CH–CH interactions lead to an in‐plane hexagonal surrounding of one molecule. While 4 forms nicely crystals, its solubility remains still very high in CH 2 Cl 2 , which is characteristic for London dispersion interactions . Even though the TBP‐skeletons show a similar distortion in all four structures, the examples show that meso ‐substituents have a distinct influence on the crystal‐packing, which allows for manifold manipulation.…”
Section: Resultsmentioning
confidence: 93%
“…Importantly,t he clusterformation ability is not related to the solubility of the molecules in for example, CH 2 Cl 2 or CHCl 3 , which does not only allow the clear analysis by NMR spectroscopy in solution (compareF igures S12-S15 in the Supporting Information), but correlates well to the latest observations by Pollice et al,w ho found the attenuation of LD in CH 2 Cl 2 solutions. [11] Aq ualitative depiction can be summarized as the following:c luster size: 4 ! 3 > 2 > 1 !…”
Section: Resultsmentioning
confidence: 99%
“…Bulky substituents like cyclohexyl, adamantly,o rtert-butyl (tBu) groups,a re often installed under the premise of Pauli repulsion, thus as sterically demanding and potentially solubilizing groups. [2,3] However,r ecent theoretical [4][5][6][7] and experimental work [8][9][10][11] led to the rise of so-called dispersion-energy-donors (DEDs). The attractive interactions based on oscillating dipole moments, called Londond ispersion (LD), [12,13] are the foundation of s-s interactions in DEDs, as they are true for tert-butyl groups.Still, on paper, tBu groups appear as bulky substituents and indeed, usually solubilizing effects are mostly observed.…”
Section: Introductionmentioning
confidence: 99%